Social media use at workplace and effects on knowledge sharing–evidence from Saudi Arabia - Hadoussa, Slim; Louati, Hanen (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
This study investigates the effects of social media use on employees’ social capital and knowledge sharing. A research model is proposed and empirically tested with an online survey study of 288 working professionals using social media at a Saudi Telecom Company. Results reveal that social media use in the workplace positively influence knowledge sharing. The findings contribute to clarify the importance of the different dimensions of Social Capital especially shared vision and trust, and their role in enhancing profitable knowledge sharing practices. This study offers effective and valuable HR policies regarding the use of social media at workplace within the MENA context.